DAMPAK PROGRAM BANTUAN PANGAN NON TUNAI TERHADAP KESEJAHTERAAN RUMAHTANGGA PETANI DI KOTA JAMBI - Herviyanti, Yunika; Hamid, Ernawati; Edison, (JALOW | Journal of Agribusiness and Local Wisdom, 2021)
This study aims to determine; 1) To describe farmers who receive Non-Cash Food Aid in Jambi City, (2) To describe the Impact of Non-Cash Food Aid on the Welfare of Farmers Recipient of Non-Cash Food Aid in Jambi City. This research was conducted in Telanaipura District and Teluk Teluk District. The research area was taken by considering that Telaipura and Danau Teluk sub-districts have the most rice farming areas in Jambi City. The data used in this study are primary data from farmer households in Jambi City and farmer households receiving Non-Cash Food Assistance. The research used descriptive statistical analysis methods and inferential analysis. The results showed that the characteristics of farmers who received Non-Cash Food Assistance in Jambi City were seen as welfare indicators set by the Central Statistics Agency in terms of income indicators, the average monthly income reached Rp 2,653,187, and the average expenditure indicator reached Rp 2,805,000, Then from the education indicators it is known that the average education of Farmers is junior high school education, then from the health indicators there are still many households that have a fairly high morbidity (illness rate), and finally the indicator of the physical condition of housing is not found RUTILAHI (Unfit House). Huni). Then, judging from the accuracy of the targets of the Non-cash Food Assistance Program, it is known that the Non-cash Food Assistance Program has precisely touched the Pre-Prosperous families in Jambi City.